The Architecture of Counter-Terrorism Legislation in India and Indonesia: An Analysis of Issues and Challenges - Bedi, Shruti; Paripurna, Amira (Universitas Airlangga, 2025)
Counter-terrorism law is a major challenge to any country since it incorporates a wide range of regulations of domestic law. Its multi-layered nature makes it imperative for academics to highlight comparative insights with a view to resolving the threat. The changes in the mode, tactics, and targets of terror attacks have evolved and become more complex; terrorist cell groups continue to grow, and the nature of terrorist networks across national borders ensures that terrorism cannot be tackled effectively by ordinary means. This paper employs comparative doctrinal research that aims to analyze and understand the similarities and differences between legal rules in India and Indonesia. This paper takes on the challenging endeavor of scrutinizing the counter-terrorism legislation of both countries. It delves into the obstacles confronted by both countries, offering systematically organized details on their current anti-terrorism legislations. The aim and objective of such discussion is to draw inspiration and perceptions from one another’s jurisdiction to evolve a better law. The result of this study shows that, in India and Indonesia, the current counter-terrorism legislation heavily supports the authority of the State, often at the expense of civil liberties for citizens. It is essential to develop a holistic counter-terrorism framework that allows the State to effectively thwart terrorists and their activities, while simultaneously safeguarding the fundamental rights.